A 10-week pedometer-based walking program induced weight loss and improved metabolic health in community-dwelling adults - Roselina Mokhtar,; Hazariah Abd Halim,; Mohd Hanif Zailani,; Afendi Isa,; Nor Farah Mohamad Fauzi, (Penerbit Universiti Kebangsaan Malaysia, 2019)
Walking 10,000 steps daily is associated with beneficial health outcomes. Recent systematic reviews have suggested that pedometers may be an effective motivational tool to promote walking. The aim of this study was to study the effectiveness of a 10-week, pedometer-based walking intervention to improve physical activity, body composition and metabolic health indices in a sample of suburban community-dwelling adults not meeting current physical activity recommendations. After screening, 34 overweight/obese individuals (mean age: 46 ± 8 years, mean BMI: 28.3 ± 4.2 kg/m2) were accepted into the walking program conducted by the Health Promotion Community Centre, Bangi. Subjects were instructed to increase their steps by 3000 steps daily above their baseline values for 10 weeks. Daily step count, body weight, BMI, waist circumference, as well as blood pressure, fasting glucose and lipids were evaluated at baseline and following the 10-week intervention. Thirty-one participants completed the program with 100% adherence. The average daily steps recorded during the 10-week intervention was 9693 ± 2196 steps per day. Mean daily steps increased from 8679 ± 2567 steps in Week 1 to 10,766 ± 3200 steps in Week 10 (p = 0.040). Overall, there were reductions in body weight (-1.13%, p = 0.010), waist circumference (-3.5%, p = 0.001) and BMI (-1.41%, p = 0.008) as well as fasting blood glucose (-8.5%, p = 0.003) and systolic blood pressure (-4.8%, p = 0.007) following the intervention. The findings of this study demonstrated that a goal-driven, pedometer-based walking intervention for 10 weeks resulted in a modest reduction in body weight and improved metabolic health outcomes in overweight/obese, community-dwelling adults.